Cognitive stimulation in socioeconomically disadvantaged children with neurodevelopmental disorders: a case series - Rodríguez-Prieto, Pablo; Giral-Oliveros, Nathalia Alejandra; Simpson, Ian Craig; Ibáñez-Alfonso, Joaquín A. (Frontiers in Psychology, 2024)
Introduction: Research shows how conditions in socio-economically disadvantaged environments can be a risk factor for children’s cognitive development. Consequently, children with neurodevelopmental disorders growing up in such environments face a double challenge. This study analyzed the effect of a comprehensive cognitive stimulation program on 4 single case studies comprising children with neurodevelopmental disorders from Guatemala. Methodology: A descriptive study was conducted, using a case series approach, consisting of four participants with neurodevelopmental disorders, and a neurotypical group of 126 children. Participants in the neurotypical group were randomly assigned to either a control or experimental reference group. Cognitive assessments were performed pre- and post-intervention for all participants. Children in the experimental group received a comprehensive cognitive stimulation program between assessments. Two participants with neurodevelopmental disorders also received the stimulation program while the other two children with neurodevelopmental disorders performed the same task as the control group, specifically, regular reading activities. Results: The experimental group exhibited a significant improvement in executive functions (inhibition, flexibility, and planning). The two experimental group children with neurodevelopmental disorders exhibited improved social cognition, showing a larger improvement compared to neurotypical children in their group, as well as compared to the two control children. However, although the reading program improved the language skills of the neurotypical control group, the children with neurodevelopmental disorders did not show as much improvement. Conclusion: These results suggest that specialized interventions are beneficial for children from socio-economically disadvantaged backgrounds, but importantly, may have a larger impact on children with neurodevelopmental disorders.